'It's just a very male industry': gender and work in UK design agencies. Issue 7 (2nd July 2016) - Reimer, Suzanne
Abstract: The article focuses upon gender divisions of labour in the UK design sector as a means of highlighting a relatively understudied segment of the creative industries. Drawing upon a wider study of design consultancy firms across London, Birmingham, Manchester and Newcastle, it considers how configurations of gender division are bound up with everyday representations of design labour. The article reveals how associations between craft, skill and masculinity appear, and are reinforced in design practice. It also points to the ways in which design work is valorised within and through constructed geographies of difference between London and the regions, emphasising that hegemonic masculinities are reinforced and reproduced in reference to understandings of activities in place.